Kreuzzeichen : Franz Bernhard - Anna Bien - Georg Csonka - Herbert Egl - Herbert Falken - Barbara Heinisch - Jan Knap - Werner Knaupp - Ulrich Meister - H.P. Taro Miyabe - Jean-Claude Mondot - Thomas Müller - Dirk Posselt - Rudolf Schoofs - Johannes Schreiter - Sam Szembek - Antoni Tàpies - Joan Trujillo. (München : Galerie an der Finkenstrasse, 1992)
Franz Bernhard - Anna Bien - Georg Csonka - Herbert Egl - Herbert Falken - Barbara Heinisch - Jan Knap - Werner Knaupp - Ulrich Meister - H.P. Taro Miyabe - Jean-Claude Mondot - Thomas Müller - Dirk Posselt - Rudolf Schoofs - Johannes Schreiter - Sam Szembek - Antoni Tàpies - Joan Trujillo
Kreuzzeichen, Galerie an der Finkenstrasse, München, 23. Oktober bis 20. November 1992
boek